NAVIGATING LAW AND LEADERSHIP IN INDIA’S VISUAL ARTS INDUSTRY: GOVERNANCE INTELLECTUAL PROPERTY AND INSTITUTIONAL STRATEGY - Sinha, Anuj Kumar; Bayan, Tridisha; Mehta, Pinki; Kaur, Jaspreet; Kulshrestha, Ruchika; Khound, Kaveri; Thomas, Subin; Middha, Minakshi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Digital transformation reconfigures the governance models of the Indian industry of visual arts between the regulation of intellectual property, institutional leadership, as well as blockchain-integrated property ownership models. Splintered enforcement, incomplete provenance recording, and participation in resale were historically limiting payments of artists and transparency in institutions. A multidimensional system of assessment of governance was created that would measure the socio-economic risk, compliance preparedness, provenance assurance, and sustainability exposure within the framework of museums, galleries, and digital space. Quantitative aggregation on the basis of scenarios of normalized indicators of governance led to the creation of composite governance scores of about 58 percent in museums, 58 percent in galleries, and 78 percent in digital platforms, reflecting a fully completed measurable efficiency in an automated royalty realization and programmable compliance platforms. Variability analysis revealed that the more digital governance is conducted, the more volatile the performance are likely to turn out to be, the uncertainty of the regulation, and the systemic risk involved. Findings analysis enables conclusions to be identified on the basis of an integrated governance paradigm to be discovered a synthesis via legal harmonization, establishment of institutional capacity, and sustainable digital compliance infrastructure. This would make the income of artists more stable in the long-term, enhance the transparency of provenance, and enhance cultural market sustainability and ethical stewardship. The manuscript contributes to the interdisciplinary forms of governance model which can be co-related to law, leadership and technology to design digitally transforming creative economies through evidence based cultural policy.